Effectiveness Of A Gratitude-Based Intervention In Increasing Subjective Well-Being Of Mothers With Down Syndrome Children - Yu, Xiaotong (2017)
The field of positive psychology is quickly emerging with a number of interventions that focus on increasing the happiness and well-being of people. Gratitude-based interventions have been found to be one of the effective interventions in many studies. This online-based study investigated the effectiveness of a 4-week intervention using gratitude lists to improve the level of gratitude and subjective well-being (SWB) in a sample of Malaysian mothers with Down syndrome children (N = 63).